Relación entre el nivel de conocimientos y las Prácticas Preventivas sobre Infecciones de Transmisión Sexual VIH-SIDA en estudiantes del 5º año de secundaria de la I.E Juan Miguel Pérez Rengifo. Junio - Agosto 2012 - Arrasco Armas, Jesús Marleny (2012)
The following research was made to determine the relationship between “the standard of knowledge and preventive practices about sexually transmitted infections HIV / AIDSin students from Juan Miguel Perez Rengifo high school, June – August 2012. The design of the research is correlational descriptive of transverse section. The sample, no probabilistic for our own interest, was seventy seven (77) students of the 5th grade from Juan Miguel Perez Rengifo high school who achieved with all our criteria of inclusion. We used the quantitative method by using questionnaire of twenty (20) questions with three (3) answers and those questions measured the knowledge in dimension of concepts, kind of STI, how to prevent, how to transmit, transmitter agents, how to care and how to diagnose; and a questionnaire of eighteen (18) questions with descriptive scale, in the dimensions of preventive practices: safe sex, sexual hygiene, and medical control with three (3) answers, to measure the preventive practices of STI – HIV / AIDS. The data processing of the descriptive statistical analysis was executed in Excel 2010 program and the analysis to check the hypothesis was executed by CHI CUADRADO test with the statistical pack SPSS 19.0. The results show us that the majority of students have a medium standard of knowledge (74.0 %) and a suitable practice (64.9%). The CHI CUADRADO test show us, there isn’t a significant relationship x2t (5.991= p>0.05) refusing our hypothesis. CONCLUSIONS.-the standard of the knowledge about STI – HIV / AIDS hasn’t a direct relationship (p > 0.05) with the preventive practice and this major knowledge is about kind of sexual transmission, obtain by the socialization with their friends as the majority have begun a sexual experience from an early age, and his confidant is another teenager, we recommend to create a curricular formative educative program about sexually transmitted diseases, with the aim to improve the preventive practices